INNOVATIVE EDUCATIONAL SUPERVISION MANAGEMENT TO IMPROVE TEACHER PERFORMANCE AND LEARNING QUALITY: A SYSTEMATIC LITERATURE REVIEW - Irda Suriani; Siti Masdalena Harahap; Suriani Br Sipahutar; Saydah Maimunah Pasaribu; Salwa Salsabillah Rambe; Aula Annada Batubara; Dinda Rosalina Siregar; Rahmadani Siregar; Dewi Sartika Nainggolan; Dini Amelia Br Tambunan; Alaida Zaskia Harahap (Literasi Nusantara, 2026)
This systematic literature review examines innovative educational supervision management practices and their contribution to enhancing teacher performance and learning quality. By synthesizing findings from recent peer-reviewed publications, the study highlights key innovative supervision approaches, including collaborative supervision, technology-assisted supervision, reflective feedback, and data-driven decision-making. The review reveals that these practices significantly improve teachers' professional competence, instructional effectiveness, and engagement in continuous professional development. Furthermore, these strategies foster stronger collaboration between school leaders and educators while encouraging the adoption of student-centered instructional models. However, successful implementation relies on supportive leadership, organizational commitment, teacher readiness for change, and sustained capacity-building programs. The study concludes that innovative educational supervision is a pivotal strategy for promoting sustainable educational quality, offering actionable insights for educational leaders and policymakers in designing adaptive supervision frameworks.